Surface Properties of NaCl and KCl in a Potassium−Sodium-Saturated System with Low-Natrium Salt - Yanfang Ma; Shouyan Huang; Xin Liu; Xujie Shi; Yongsheng Du; Haining Liu (Separations)
With the continuous development of the potash industry in salt lakes, the preparation of low-natrium salt for the green and environmentally friendly utilization of potassium and sodium resources in salt lakes has become a research hotspot. The primary method involves obtaining potassium brine from salt-lake brine through evaporation and then subjecting this mineral to transformation crystallization to obtain low-natrium salt crystals. In the crystallization vessel, a potassium−sodium-saturated solution is introduced, followed by the addition of an appropriate amount of water and solid magnesium chloride. After a thorough reaction, the solid−liquid separation yields the target product of low-natrium salt. Subsequently, the surface properties of KCl and NaCl crystals were calculated using first-principles methods. The research findings revealed that potassium chloride crystals, when they contained defects, readily adsorbed Na+ and NaCl. In a sodium−potassium-saturated system, KCl and NaCl easily formed heterojunctions, leading to embedded crystallization as the Mg2+ concentration increased in this saturated system. Feed rate and residence time directly affect the purity of low-natrium salt. A low-natrium salt meeting the requirements can be obtained after a residence time of more than 80 min under the following conditions.